An examination of the relationship between frontline employees' perceptions of people management practices and their prosocial service behaviours: a case study of an employee-owned organization - Bardhan Correia, Debarpita (Cranfield University, 2015)
With a growing body of literature examining HR systems’ influence on organizational performance outcomes, there has been a plea for research that examines the underlying mechanisms that facilitate this in a service setting. This study adopts the notion of people management which incorporates the management of HR implementation and line managers’ leadership behaviour in its investigation of how HR affects performance. This study, by examining how frontline employees’ perception of people management practices affects individual level prosocial service behaviours, and by using a qualitative approach in data collection and analysis, offers an explanation of the underlying mechanisms in the causal chain. Furthermore, the setting of this research in an employee-owned organization affords a context- rich account of how HR systems affect individual level performance in a service setting. Thirty one semi-structured interviews were conducted, of which twenty three were conducted with frontline employees to elicit how their experiences of people management practices affected their display of prosocial service behaviours. Eight semi-structured interviews were arranged with frontline managers to offer an alternate perspective to data gathered from the employees. The research identifies bundles of practices, comprising both “employment” and “work practices” as instrumental in employees’ display of prosocial service behaviours. The results confirm the AMO framework as being a suitable explanation of mediating mechanisms in the HR-performance chain, whilst not only confirming the presence of a few existing intervening influences but also identifying novel factors not previously studied within the HR-performance discussion. It also demonstrates that adopting multiple theoretical perspectives in investigating HR-performance relationships offers a more comprehensive picture. Finally, the research confirms the role of the line manager as a protagonist within the HR- performance discussion whilst also demonstrating the significance of co-workers. The ownership context emerges as important in this enquiry – specifically work atmosphere and relationships – in influencing employees’ service behaviour.